EFEKTIVITAS SISTEM SHIFTING PADA ERA NEW NORMAL DI BALAI PEMASYARAKATAN KELAS I MAKASSAR - Fitriana. H; Muhammad Tahiri; Sitti Rahmawati Arfah (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2022)
This study purposed to find out the effectiveness of the employee shifting system in the new normal era at the Makassar Class I Correctional Center by using a qualitative type of phenomenological research. The informants consisted of 6 civil servants at the Makassar Class I Correctional Center. Research data obtained through observation, interviews, documentation and media review. Validation of data by triangulation of sources, techniques and time were analyzed through data reduction techniques, data presentation and conclusions. The results showed that the implementation of the shifting work from home (WFH) and work from office (WFO) systems for employee performance had run effectively, which could be seen in terms of the time or working hours of the employees, which continued the same as the usual day so that the work could be completed. on time, in terms of the goals or objectives of the shifting system so that employee performance could still run, whether it was carried out from home or the office and in terms of employee health which was more secure because they did their work while still adhering to strict health protocols so that the spread of Covid 19 could be minimized.